Atividades das colinesterases em ratos infectados experimentalmente por Sporothrix schenckii - Castro, Verônica Souza Paiva (2015)
Sporotrichosis is an implantation mycose, caused by species complex Sporothrix spp., considered the subcutaneous mycosis with higher occurrence and importance in the Americas, this thermally dimorphic fungus induces a chronic inflammatory granulomatous response in their hosts. The cholinesterase, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are the "key" enzimes signal in inflammatory and immune processes, for regulating the levels of ACh, the main neurotransmitter "cholinergic antiinflammatory pathway". The cholinesterase activity has been demonstrated in various inflammatory conditions; however, there is no evidence of his participation in sporotrichosis. The objective of this study was to report a case of feline sporotrichosis by natural infection; evaluate the activities of AChE in the lymphocytes and whole blood; evaluate the activity of BChE; cytokines (IL1, IL6, TNF, and IL-10 INFγ) and immunoglobulins (IgA, IgG, IgM, IgE) in serum of rats experimentally infected with S. schenckii. Sixty-three rats were divided into three groups, control group (CG), group by subcutaneous infection (GSC) and group by intraperitoneal infection (GIP). Blood collection for activities evaluation of cholinesterase, cytokines and immunoglobulins were held on 15, 30 and 40 post-infection (PI). The GIP, had an increase in the activity of AChE in the blood in all experimental times, the increase in lymphocytes occurred only on 30 and 40 days PI. The increase of the enzyme suggests a decrease in the levels of ACh with consequently increased IL-1, IL-6, TNF-α, INF-γ, as observed in this study. In the acute phase of infection wants an intense inflammatory response in an attempt to remove the agent. However, with the chronicity of infection if the stimulus is maintained can lead to remarkable tissue injury. Regarding the chronic process observed in GIP, 30 and 40 days PI, that IL-10 was shown to be increased, but not enough to contain inflammation, as pro cytokines, continued high levels. Conversely, what happened in the GIP, the SC group had reduced levels of IL-10 at all times PI, this decrease can lead to tissue damage by not blocking the inflammatory response. The activity of AChE in the GSC only statistically increased in lymphocytes, at 40 days PI. There was no significant activity when assessing the BChE, in both groups, except in the GSC 40 days PI. The BChE is not efficient in Ach s hydrolysis in low concentrations, but it can replace the AChE when itself is inhibited. High levels of immunoglobulins in all groups and at all times, shows the induction of humoral immune response in sporotrichosis. Thus, the increase in the AChE activity in whole blood and lymphocytes, together with high levels of serum immunoglobulins and cytokines, suggesting the involvement of cholinesterases, and in immune cell response against infection by S. schenckii.